Cheating at solitaire a Gregor Demarkian novel - Haddam, Jane (New York : St. Martin's Minotaur, 2008)
Former FBI agent Gregor Demarkian, fleeing from his own wedding preparations, is hired to review a case--one that he finds has little evidence and twisted by an out-of-control media--in what may be the most compelling case of his entire career.
Keywords: Demarkian, Gregor (Fictitious character); Private investigators -- Massachusetts; Armenian Americans; Celebrities; Massachusetts; Mystery fiction